The Effect of Reading Aloud Strategy for Developing Reading Habits - Naomi Dalila Malau; Erni Erni; Dahnilsyah Dahnilsyah (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this study is to determine whether or not the reading aloud technique aided eighth-grade junior high school students in developing reading habits. This is pre-experimental quantitative research. The instruments utilized in this study will be a test and a questionnaire. This study's population included 56 students from two classes, with 29 serving as the sample. The data was collected in the classroom using a reading-aloud activity. Descriptive and inferential statistics were utilized to analyze the data from the reading aloud application, as well as questionnaire analysis to assess the students' reading habits. The data demonstrated that majority of the students in the classroom were acquiring reading habits as a result of Reading Aloud. Strategy was applied and it proved that the Reading Aloud Strategy was effective to develop the students’ reading habits. Based on the findings, it is therefore recommended among others that students should start to apply this strategy in case to develop their reading habits which are useful for their future and it was recommended that teachers should help students pay more attention to their reading attitude. It can be done by providing a variety of books, encouraging independent reading, or organizing class activities. And the teacher encourages their students to read extensively.